1994
DOI: 10.1055/s-2006-959461
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of the Garlic CompoundS-Allylcysteine

Abstract: The pharmacokinetic behavior of S-allylcysteine (SAC), one of the biologically active transformation products from garlic, was investigated after oral administration to rats, mice, and dogs. SAC was rapidly and easily absorbed in the gastrointestinal tract and distributed mainly in plasma, liver, and kidney. The bioavailability was 98.2, 103.0, and 87.2% in rats, mice, and dogs, respectively. SAC was mainly excreted into urine in the N-acetyl form in rats; however, mice excreted both SAC and the N-acetyl form.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
95
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(109 citation statements)
references
References 3 publications
11
95
1
2
Order By: Relevance
“…The maximum plasma concentration of SAC has also been reported to be >200 Amol/L after p.o. administration of a 50 mg/kg dose to rats (35). Therefore, the organosulfur compound concentrations we used in our cell culture studies are comparable with those seen in the serum of animals and to those used in previous cell culture assays (36).…”
Section: Discussionsupporting
confidence: 59%
“…The maximum plasma concentration of SAC has also been reported to be >200 Amol/L after p.o. administration of a 50 mg/kg dose to rats (35). Therefore, the organosulfur compound concentrations we used in our cell culture studies are comparable with those seen in the serum of animals and to those used in previous cell culture assays (36).…”
Section: Discussionsupporting
confidence: 59%
“…It is unclear if such concentrations of DATS are achievable in humans because of lack of pharmacokinetic data on this agent. However, the pharmacokinetics of S-allylcysteine, a water soluble OSC analog, has been studied in rodents and dogs (Nagae et al, 1994). This study showed that S-allylcysteine was absorbed rapidly, and reached peak plasma concentration within 0.5-1 h. The plasma concentrations following oral administration of 12.5, 25 and 50 mg S-allylcysteine/kg body weight were about 50, 112 and 227 mM, respectively (Nagae et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…However, the pharmacokinetics of S-allylcysteine, a water soluble OSC analog, has been studied in rodents and dogs (Nagae et al, 1994). This study showed that S-allylcysteine was absorbed rapidly, and reached peak plasma concentration within 0.5-1 h. The plasma concentrations following oral administration of 12.5, 25 and 50 mg S-allylcysteine/kg body weight were about 50, 112 and 227 mM, respectively (Nagae et al, 1994). Thus, it is possible that the concentrations of DATS required to inhibit cell proliferation and cause cell cycle arrest and apoptosis may be achievable in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic studies demonstrate fast absorption and distribution phases followed by a slow elimination phase for oral administration, as well as fast distribution and slow elimination phases for i.v. administration (Nagae et al, 1994;Yan & Zeng, 2005). Pharmacokinetics of S-allylcysteine in humans by oral garlic administration revealed a half-life of 10 h and clearance time of 30 h (Kodera et al, 2002), suggesting a high bioavailability.…”
Section: Presumable Protective Effect Of Garlic Compounds In Cerebralmentioning
confidence: 98%